Pengaruh Penerapan Strategi Systemic Approach Teaching and Learning (SATL) Terhadap Pemahaman Konseptual Siswa Kelas X Pada Materi Tata Nama Senyawa dan Persamaan Reaksi - Hayyun Lisdiana; Tritiyatma Hadinugrahaningsih; Sabilla Yaumil Nurlaily Al Ashary (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
This research aims to determine the effect of appliying the Systemic Approach Teaching and Learning (SATL) strategy on the conceptual understanding of grade X students on the material of compound names and reaction equations. The research was conducted in the even semester of the 2023/2024 academic year at SMA Negeri 68 Jakarta. The type of research used is quantitative research with quasi experimental method and with a Pretest Posttest Nonequivalent Control Group Design. The research sample was obtained through purposive sampling technique with class X-2 serving as the experimental class which used the Systemic Approach Teaching and Learning (SATL) strategy using the problem based learning (PBL) model and class X-4 serving as the control class which used problem based learning (PBL) model without using strategy. The results showed that the average posttest of the experimental class (85,71) was higher than control class (76,91). Based on the results of the U Mann Whitney test calculation, the Asymp.Sig.(2-tailed) value is 0,047 so it can be concluded that 0,047<0,05 which means that H0 is rejected. Based on the results obtained, it can be concluded that the application of Systemic Approach Teaching and Learning (SATL) strategy has a positive effect on the conceptual understanding of class X students on the material of Compound Names and Reaction Equations.